The Association Between Serum Isthmin-1 and Disease Activity, Inflammation, and Autoantibody Status in Rheumatoid Arthritis - Oz, Burak; Gunduz, Ibrahim; Yamancan, Gulsah; Dogan, Yusuf; Akkoc, Ramazan Fazil; Gozel, Nevzat; Koca, Suleyman Serdar (Mdpi, 2025)
Background/Objectives: Isthmin-1 (ISM1) is a secreted protein involved in immune regulation, inflammation, and angiogenesis. Although ISM1 has been implicated in chronic inflammatory conditions, its clinical relevance in rheumatoid arthritis (RA) remains unknown. This study aimed to evaluate serum ISM1 levels in RA patients and assess their associations with disease activity, autoantibody status, and inflammatory markers. Methods: This cross-sectional study included 90 RA patients fulfilling the 2010 ACR/EULAR criteria and 30 age- and sex-matched healthy controls. Serum ISM1 concentrations were measured using ELISA. Disease activity was assessed using DAS28-CRP and DAS28-ESR. Statistical analyses included group comparisons, correlation testing, multivariate linear regression, and ROC curve analysis to evaluate the predictive performance of ISM1 for remission or low disease activity. Results: Serum ISM1 levels were significantly lower in RA patients than in controls (454 +/- 378 vs. 972 +/- 809 ng/L, p < 0.001). ISM1 concentrations were inversely correlated with CRP, ESR, and both DAS28 indices. Multivariate regression confirmed independent associations between lower ISM1 concentrations and higher disease activity. ISM1 levels were significantly reduced in RF- and anti-CCP-positive patients, as well as in treatment-naive early RA. ROC analysis identified a cut-off value of 673.73 ng/L for predicting remission or low disease activity, with an AUC of 0.713 (95% CI: 0.596-0.820), 100% specificity, and 38.9% sensitivity. Conclusions: This study is the first to demonstrate that serum ISM1 is independently associated with disease activity and autoantibody positivity in RA. High ISM1 levels may serve as a specific indicator of clinical remission or low disease activity, supporting its potential as a non-invasive biomarker for disease monitoring.
Keywords: rheumatoid arthritis; Isthmin-1; disease activity; autoantibodies; DAS28; biomarker; adipokine